2017
DOI: 10.1080/10942912.2016.1239632
|View full text |Cite
|
Sign up to set email alerts
|

Residual nitrite and biogenic amines of traditional northeast sauerkraut in China

Abstract: The safety of northeast sauerkraut (NS) has always been a concern in China. In the present study, the nitrite and biogenic amine (BA) contents in 378 NS, collected or purchased from Chinese families and markets (including morning markets and local supermarkets), were measured. The results showed that the nitrite and BA contents of samples from Chinese families and some morning markets were higher than those from local supermarkets. The highest level of nitrites was 38.5 ± 5.2 mg/kg in unpackaged NS from Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It was reported that putrescine, tyramine, cadaverine, histamine and tryptamine constitute a major part of BA profiles in sauerkraut [ 6 , 15 ]. This study found six common BAs with different contents in FM samples ( Table 3 ), including tryptamine (11.02–35.74 mg/kg), putrescine (3.79–39.71 mg/kg), cadaverine (0–97.92 mg/kg), histamine (1.43–213.13 mg/kg), tyramine (0–37.85 mg/kg), and spermidine (0–3.39 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that putrescine, tyramine, cadaverine, histamine and tryptamine constitute a major part of BA profiles in sauerkraut [ 6 , 15 ]. This study found six common BAs with different contents in FM samples ( Table 3 ), including tryptamine (11.02–35.74 mg/kg), putrescine (3.79–39.71 mg/kg), cadaverine (0–97.92 mg/kg), histamine (1.43–213.13 mg/kg), tyramine (0–37.85 mg/kg), and spermidine (0–3.39 mg/kg).…”
Section: Resultsmentioning
confidence: 99%
“…Mesenteroides were found to be able to metabolize nitrite [ 25 ]. Furthermore, it was reported that enzymatic activity and microbial metabolism were influenced by some ingredients in fermented vegetables, such as salt, sugar, ginger and garlic, which could change the nitrite contents during the fermentation process [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations